1993
DOI: 10.1085/jgp.101.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Actions of cholinergic drugs in the nematode Ascaris suum. Complex pharmacology of muscle and motorneurons.

Abstract: A B S T R A C T The cholinergic agonists acetylcholine (ACh), nicotine, and pilocarpine produced depolarizations and contractions of muscle of the nematode Ascaris suum. Dose-dependent depolarization and contraction by ACh were suppressed by about two orders of magnitude by 100 ~M d-tubocurarine (dTC), a nicotinic antagonist, but only about fivefold by 100 p-M N-methyl-scopolamine (NMS), a muscarinic antagonist. NMS itself depolarized both normal and synaptically isolated muscle cells. The muscle depolarizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…In an isolated muscle bag preparation of A. suum, Martin and Valkanov (1996) observed evidence of a mecamylamineresistant cholinergic receptor, stimulation of which increased the opening of a non-selective cation channel, an effect that was not blocked by atropine, mecamylamine or tubocurarine. In addition Segerberg and Stretton (1993) reported that pilocarpine, a muscarinic agonist, produced a concentration-dependent depolarization in A. suum muscle that was not antagonized by a muscarinic antagonist (N-methyl-scopolamine) nor the nicotinic antagonist, tubocurarine. The lack of effect of oxtremorine and atropine in previous A. suum studies, together with the modest effect of atropine in our studies, suggests that a GAR-3-like receptor is not involved in mediating the effects of MFI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an isolated muscle bag preparation of A. suum, Martin and Valkanov (1996) observed evidence of a mecamylamineresistant cholinergic receptor, stimulation of which increased the opening of a non-selective cation channel, an effect that was not blocked by atropine, mecamylamine or tubocurarine. In addition Segerberg and Stretton (1993) reported that pilocarpine, a muscarinic agonist, produced a concentration-dependent depolarization in A. suum muscle that was not antagonized by a muscarinic antagonist (N-methyl-scopolamine) nor the nicotinic antagonist, tubocurarine. The lack of effect of oxtremorine and atropine in previous A. suum studies, together with the modest effect of atropine in our studies, suggests that a GAR-3-like receptor is not involved in mediating the effects of MFI.…”
Section: Discussionmentioning
confidence: 99%
“…Colquhoun et al (1991) have tested a range of cholinergic agonists on the electrophysiology of A. suum muscle cells and found furtrethonium to be one of the more potent muscarinic agonists. Segerberg and Stretton (1993) have also found evidence of muscarinic-like receptors on A. suum muscle mediating depolarization and contraction; and Martin and Valkanov (1996) have described effects of acetylcholine potentiating the opening of mecamylamineresistant non-selective cation channel currents (I bcat ) in isolated A. suum muscle bags. In Caenorhabditis elegans three G-protein coupled acetylcholine receptors (GAR-1, GAR-2 and GAR-3) have been reported (Hwang et al, 1999;Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Like GABA, glutamate has been proposed to play roles in the nervous system of the most primitive animals. Antagonistic to GABA, glutamate increases the outputs of ectodermal and endodermal impulse generating systems in the phylogenetically basal hydrozoan Hydra vulgaris (Kass-Simon et al, 2003), and acts as an excitatory neurotransmitter in cestode and aplysiidae nervous systems (Davis & Stretton, 1995;Verma et al, 2010;Gerschenfeld, 1973;Kehoe & Marder, 1976;Segerberg & Stretton, 1993). Glutamate is the main excitatory neurotransmitter in the nervous systems of nematodes and fruit fly (Devaud et al, 2008).…”
Section: Gaba and Glutamate As Neurotransmitters Exist In Early Animamentioning
confidence: 99%
“…ACh acts at muscarinic receptors, encoded in nematodes by the gar genes Lee et al, 1999Lee et al, , 2000. These are present in parasitic species, and have atypical muscarinic pharmacology (Segerberg and Stretton, 1993;Kimber et al, 2009), which again suggest that helminth-specific molecules could be developed.…”
Section: G Protein-coupled Receptorsmentioning
confidence: 99%